(3GdCNHGQ GdWhGds - (3CMeO Hf OGhO Hf hffO GdOjfhQj, CHh MfjaI , GdOjfhQj,J (B282 (3g` s ((3GdeaVd Hf LYaQ s)
(3ChdgG (B:s
(3bGd CHh MfjaI CMeO Hf OGhO QMeg Gddg (B: (3hLOJ ajeG cJH Cgd GdYde HGdCNHGQ GdChdi Cf BOe cGf GdN s
(3BNQgG (B:s
(3hQLY Edi GdchaI hJgjC dbJGd Cgd GdTGe acGf efg hef eYGhjI HUajf eG cGf , hGddg CYde HGdRjGOI hGdfbUGf , hMSHfG Gddg hMOg hfYe Gdhcjd hGdeYjf , hUdhGJg Ydi NjQ Ndbg SjOfG eMeO GdfHi hBdg hGdWGgQjf s
(3fSNI fajSIs
(3hGdejcQajde Hg Jda HSjWs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B123s
Keywords: (3GdJGQjNs